2016
DOI: 10.1007/s10346-016-0696-4
|View full text |Cite
|
Sign up to set email alerts
|

Tsunamis generated by landslides at the coast of conical islands: experimental benchmark dataset for mathematical model validation

Abstract: This paper presents a new experimental campaign aimed at reproducing tsunamis generated by landslides at the flank of conical islands. In order to describe in high details the wave field around the island a special acquisition system, which consists of both fixed and movable wave gauges, has been employed. Indeed, each experiment has been repeated several times by changing the configuration of the movable gauges, then obtaining a single virtual experiment with high spatial resolution measurements. Fixed run-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 33 publications
6
27
0
Order By: Relevance
“…The maximum runup and rundown heights decay as the radial distance from the source increases and a localized amplification occurs on the lee side of the conical island scenario. Similar results were observed using block landslides by Lynett and Liu [2005], Di Risio et al [2009a,2009b], Romano et al [2013Romano et al [ , 2016, and Heller and Spinneken [2015]. Generally the maximum rundown in the impact region is larger than the runup given the large water level drawdown caused by the landslide impact.…”
Section: Lateral Maximum Runup and Rundownsupporting
confidence: 73%
See 3 more Smart Citations
“…The maximum runup and rundown heights decay as the radial distance from the source increases and a localized amplification occurs on the lee side of the conical island scenario. Similar results were observed using block landslides by Lynett and Liu [2005], Di Risio et al [2009a,2009b], Romano et al [2013Romano et al [ , 2016, and Heller and Spinneken [2015]. Generally the maximum rundown in the impact region is larger than the runup given the large water level drawdown caused by the landslide impact.…”
Section: Lateral Maximum Runup and Rundownsupporting
confidence: 73%
“…[], Romano et al . [], and Heller and Spinneken []. Generally the maximum rundown in the impact region is larger than the runup given the large water level drawdown caused by the landslide impact.…”
Section: Lateral Wave Runupmentioning
confidence: 99%
See 2 more Smart Citations
“…Ataie-Ashtiani and Malek-Mohammadi [14] analyzed the wave period, height, and energy of the surge and developed an empirical equation for the period and height of the surge wave. Recently, the wave generation problem caused by a coastal tsunamigenic source, that is, a coastal mountain landslide, has been solved using experiments [37][38][39] in the case of both a straight coast and a circular island, and it was found that the location of the maximum run-up along the coast occurs in the near distance (about 2-3 times the width of the landslide) rather than very close to the landslide [10].…”
Section: Introductionmentioning
confidence: 99%